Essential Roles of the Chromatin Remodeling Factor Brg1 in Spermatogenesis in Mice - Wang, Jianguan (Society for the Study of Reproduction, Inc., 2012)

(untitled)
Mammalian spermatogenesis is a complex process that involves spatiotemporal regulation of gene expression and meiotic recombination, both of which require the modulation of chromatin structure. Proteins important for chromatin regulation during spermatogenesis remain poorly understood. Here we addressed the role of BRG1, the catalytic subunit of the mammalian Swi/Snf-like BAF chromatin-remodeling complex, during spermatogenesis in mice. BRG1 expression is dynamically regulated in the male germline, being weakly detectable in spermatogonia, highly expressed in pachytene spermatocytes, and turned off in maturing round spermatids. This expression pattern overlaps that of Brm, the Brg1 homolog. While Brm knockout males are known to be fertile, germline-specific Brg1 deletion completely arrests spermatogenesis at the midpachytene stage, which is associated with spermatocyte apoptosis and apparently also with impaired homologous recombination and meiotic sex chromosome inactivation. However, Brg1 is dispensable for gammaH2AX formation during meiotic recombination, contrary to its reported role in DNA repair in somatic cells. Our study reveals the essential role of Brg1 in meiosis and underscores the differences in the mechanisms of DNA repair between germ cells and somatic cells.